ESTABLISHING THE KEY ELEMENTS OF INCORPORATION AND OUTCOMES OF 4TH INDUSTRIAL REVOLUTION IN BUILT ENVIRONMENT EDUCATION: A MIXED BIBLIOGRAPHIC AND BIBLIOMETRIC ANALYSIS - Alireza MOGHAYEDI; Karen Le Jeune; Mark Massyn; Christiana Ekpo (Journal of Construction Project Management and Innovation)
The rapid, exponential fusion of technologies which profoundly disrupts all industries and processes is commonly described as the Fourth Industrial Revolution (4th IR). The Built Environment (BE) sector has long been overdue for radical transformation that is symphonious with global trends. Consequently, how to incorporate 4th IR in BE education remains challenging. This research aims to establish what educational methods, context, tools, and technological pedagogy are required and should be adopted, as well as what the effects and outcomes can be expected from the incorporation of the 4th IR concepts in BE education. The rationale for this research stems from the aspiration to meet the United Nation Sustainable Development Goals, which advocate that young people need to be "future-ready" and this includes digital fluency and ICT literacy. The study utilised a verifiable and reproducible systematic literature review of digital education; with analysis and scrutiny of 582 academic articles for the co-occurrence of keywords, using a mixed bibliographic and bibliometric method. Through clustering analysis based on the bibliometric method, the key elements, outcomes, and their interconnections of incorporating 4th IR in BE education were outlined. The paper revealed that, in adopting 4th IR, Higher education, Design, Innovation and Privacy appear to be the predominant context. Distance education, Collaborative learning and Digital learning are the foremost education methods. Digital technologies, Virtual reality and cloud computing are the most significant education tools and technology elements. Sustainable education, Ethical learning and Student engagement are the resultant primary outcomes of incorporating 4th IR in built environment education. In addition, the results of the interconnections of indicators analysis revealed Higher education, Distance education and Sustainable education are significantly intertwined with Digital technologies. Based on the taxonomy of key elements and outcomes and the analysis of their interconnections, a conceptual framework for adopting 4th IR in built environment education was developed